Phase-fitted and amplification-fitted higher order two-derivative Runge-Kutta method for the numerical solution of orbital and related periodical IVPs - Ahmad, Nur Amirah; Senu, Norazak; Ismail, Fudziah (Hindawi Publishing Corporation, 2017)
A phase-fitted and amplification-fitted two-derivative Runge-Kutta (PFAFTDRK) method of high algebraic order for the numerical solution of first-order Initial Value Problems (IVPs) which possesses oscillatory solutions is derived. We present a sixth-order four-stage two-derivative Runge-Kutta (TDRK) method designed using the phase-fitted and amplification-fitted property. The stability of the new method is analyzed. The numerical experiments are carried out to show the efficiency of the derived methods in comparison with other existing Runge-Kutta (RK) methods.